2017
DOI: 10.1002/nme.5588
|View full text |Cite
|
Sign up to set email alerts
|

Extension of MITC to higher‐order beam models and shear locking analysis for compact, thin‐walled, and composite structures

Abstract: A class of mixed interpolated beam elements is introduced in this paper under the framework of the Carrera Unified Formulation to eliminate the detrimental effects due to shear locking. The Mixed Interpolation of Tensorial Components (MITC) method is adopted to generate locking-free displacement-based beam models using general 1D finite elements. An assumed distribution of the transverse shear strains is used for the derivation of the virtual work, and the full Gauss-Legendre quadrature is used for the numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…where denotes an implicit summation and varies from 1 to − 1. , , and are the strain components coming from the geometrical relations in (3) evaluated at the -th tying point and are the assumed interpolating functions. Their expressions as functions of the natural beam element coordinate ∈ [−1, 1] can be found in Carrera et al [36] and they are reported below. For linear elements, the interpolation is reduced to a point evaluation, since…”
Section: Shear and Membrane Locking: Mitc Beam Elementsmentioning
confidence: 99%
“…where denotes an implicit summation and varies from 1 to − 1. , , and are the strain components coming from the geometrical relations in (3) evaluated at the -th tying point and are the assumed interpolating functions. Their expressions as functions of the natural beam element coordinate ∈ [−1, 1] can be found in Carrera et al [36] and they are reported below. For linear elements, the interpolation is reduced to a point evaluation, since…”
Section: Shear and Membrane Locking: Mitc Beam Elementsmentioning
confidence: 99%
“…Moreover, in this analysis case the MITC (Mixed Interpolation of Tensorial Components) approach has been used for the HLE models to compute the shear stresses. This formulation is based on the assumed interpolation of the shear components of the stress tensor and its implementation on CUF models as well as its numerical performances when applied to higher-order theories are presented in Carrera et al [49]. In view of the results obtained for the L-angle beam, the following remarks can be made:…”
Section: L-angle Beammentioning
confidence: 99%
“…A solid Nastran model has been included for comparison purposes. MITC4 beam models, developed in [49], have been also used to assess the solutions. The solutions of displacements and normal stresses show a good agreement with the ones obtained through the solid model as the polynomial order of the theory increases.…”
Section: Wing Structurementioning
confidence: 99%
“…Wang ve Wang [7] ve Gao ve Wang [8] tarafından önerilen geliştirilmiş kiriş teorisi, dördüncü mertebeden bir diferansiyel denklem ve ikinci mertebeden bir transandant denklemden oluşmasına karşın, bu kompleks kiriş teorisi ankastre uç için yer değiştirme kısıtlarını düzgün bir şekilde ele almakta yetersiz kalmaktadır. Literatürde, kayma düzeltme faktörü, varyasyonel asimptotik çözüm, genelleştirilmiş kiriş teorisi ve kesit çarpılması gibi yüksek mertebe etkileri dikkate alan diğer çalışmalar da mevcuttur [9][10][11][12][13][14].…”
Section: Introductionunclassified